Pengaruh Pelatihan, Kepemimpinan Dan Pengembangan Sumber Daya Manusia Terhadap Prestasi Kerja (Studi kasus pada Karyawan PT. Adhiguna Putera Cabang Paiton Probolinggo) - Mohamad Fausen; Abdul Kodir Djaelani; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This research was conducted at PT Adhiguna Putera on Jl. Mawar No.03, Besuki, kec. Besuki, Kab. Situbondo. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of training, leadership and human resource development on job performance. The independent variables used are training, leadership and human resource development, while the dependent variable is work performance. The sample used in this study were 45 respondents who are employees of PT. Adhiguna Putera Paiton Probolinggo Branch. Data collection techniques using a questionnaire. The analytical method used is the instrument test, multiple linear regression analysis, classical assumption test, determination test, f test and t test using SPSS 16.0 computer software for data processing. The results of this study indicate that training affects work performance, leadership affects work performance and human resource development affects work performance. training, leadership and human resource development simultaneously affect work performance. Keywords : Training, Leadership, Human Resource Development and Work Performance.